Recent developments on sewage sludge pyrolysis and its kinetics: Resources recovery, thermogravimetric platforms, and innovative prospects. (July 2021) - Naqvi, Salman Raza; Tariq, Rumaisa; Shahbaz, Muhammad; Naqvi, Muhammad; Aslam, Muhammad; Khan, Zakir; Mackey, Hamish; Mckay, Gordon; Al-Ansari, Tareq
Highlights: A review on sources and composition of sewage sludge for pyrolysis. Thermal degradation studies and behavior of sewage sludge using TGA. Review of mechanism and principles of pyrolysis process for sewage sludge. Comprehensive discussion on the selection of kinetic models for scale up. Application of machine learning tool forprediction of kinetic data. Abstract: Sewage sludge is a by-product of the wastewater treatment process, which has the potential to be a source of transport fuels, heat, and power using the pyrolysis process. Considering the prevalence and disposal issues associated with sewage sludge, the objective of this study is to critically review the recent advancements in sewage sludge pyrolysis and its kinetics obtained using the thermogravimetric techniques, and other associated different kinetic models documented in the literature. The study will identify optimum operating conditions and design parameters to obtain high yields. The state-of-the-art perspectives and the challenges associated with full-scale implementation are highlighted for biofuels and resource recovery from the sewage sludge. Furthermore, machine-learning approaches in thermal kinetics of pyrolysis are presented and discussed in terms of their effectiveness in predicting thermal kinetics data. Finally, the challenges for a successful implementation and commercial viability of sewage sludge pyrolysis are discussed.